Tinjauan Pelaksanaan Informed Consent pada Layanan Kesehatan Praktik Kerja Lapangan Mahasiswa Fisioterapi - Zainal Abidin; Kuswardani Kuswardani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The health services that will be provided must go through stages of approval from the patient verbally or in writing, so as not to violate the patient's rights as consumers of services and is one of the obligations of the health worker himself. This research aims to determine the implementation of informed consent in health services provided by physiotherapy students during field work practice in health institutions. This research also uses a sociological juridical method, which is the result of drawing conclusions as a result of connecting cause and effect variables in accordance with social science design. From the results of this research, it was found that physiotherapy students at Widya Husada University, Semarang, during field work practice in health institutions, always gave informed consent to patients before providing health services, either verbally or in writing. Students cannot yet be called full-fledged health workers, but when students practice field work in health institutions and provide health services to patients, they are required to provide informed consent to the patient first as a form of approval for the patient's actions.